Food residues as indicators of processed plants in hunter-gatherers’ pottery from La Pampa (Argentina) - Musaubach, María Gabriela (2016)
This paper presents the results of archaeobotanical studies of plant microremains adhered to the surfaces of charred cooking-pot residues, corresponding to a context of hunter-gatherer societies in semiarid environments (Western Pampa, Argentina). Microparticles (starch granules, phytoliths, micro-charcoal, ochre-coloured organic matter and fungal remains) were identified, and the taphonomic factors that affected the plant microremains were described. Results indicate the use of ceramic containers for processing wild plants (Poaceae and Prosopis sp.), cultivated plants (Zea mays L.) and other ingredients. This study suggests the importance of plants in the diet of Pampean hunter-gatherers and the effective use of ceramic containers for processing and preparation of these resources.